Adorno on Schenker: Reconstructing the Formation of a Critique. (17th December 2020) - WEDLER, SEBASTIAN
ABSTRACT: Since the publication in 1982 of Theodor Adorno's late lecture 'On the Problem of Musical Analysis', it has been well established that Adorno had an ambivalent attitude towards Heinrich Schenker's analytical method, to the extent that the two men are usually thought of as antagonists while sharing the same concern for a work‐immanent understanding of the content of music. Yet beyond this lecture, surprisingly little is known about Adorno's actual engagement with Schenker's writings. The aim of this article is twofold. First, drawing on hitherto unexamined sources held at the Theodor W. Adorno Archiv in Frankfurt am Main, this essay reconstructs and examines Adorno's engagement with Schenker's ideas and the work of two of the theorist's most influential advocates, Felix Salzer and Oswald Jonas. Based on this, secondly, the article places Adorno's ambivalent attitude towards Schenker's method within the broader scholarly and political debates of his time. In particular, it will be argued that Adorno's reception of Schenker can be understood in relation to three discursive concerns: (1) advocating the importance of Schoenberg's music‐theoretical thought, (2) questioning the methodological reorientation of postwar Austro‐German musicology and (3) reinforcing his opposition to positivism in the domain of musical analysis. In this way, this article aims to contribute to ongoing efforts to reconstruct and understand more fully the history of Schenker reception.